Association between plantar flexor muscle volume and dorsiflexion flexibility in healthy young males: ultrasonography and magnetic resonance imaging studies - Tadashi Suga; Masafumi Terada; Keigo Tomoo; Yuto Miyake; Takahiro Tanaka; Hiromasa Ueno; Akinori Nagano; Tadao Isaka (BMC, 2021)
Abstract Background Although joint flexibility is important for human locomotion, the determinants of joint flexibility are not fully understood. In this study, we examined the relationship between dorsiflexion flexibility and plantar flexor muscle size in healthy young males. Methods and results The dorsiflexion flexibility was assessed using range of motion (ROM) and stiffness during active and passive dorsiflexion. Active ROM was defined as the maximal angle during voluntary dorsiflexion. Passive ROM was defined as the angle at the onset of pain during passive dorsiflexion. Passive stiffness was calculated as the slope of the linear portion of the torque-angle curve between 10º and 20º dorsiflexion of the ankle during passive dorsiflexion. In the first study, the plantar flexor muscle volume (MV) in 92 subjects was estimated on the basis of the lower leg length and plantar flexor muscle thickness, as measured using ultrasonography. The estimated plantar flexor MV correlated significantly with active ROM (r = -0.433), passive ROM (r = -0.299), and passive stiffness (r = 0.541) during dorsiflexion (P = 0.01 for all). In the second study, the plantar flexor MV in 38 subjects was measured using magnetic resonance imaging. The plantar flexor MV correlated significantly with plantar flexor active ROM (r = -0.484), passive ROM (r = -0.383), and passive stiffness (r = 0.592) during dorsiflexion (P = 0.05 for all). Conclusions These findings suggest that a larger plantar flexor MV is related to less dorsiflexion flexibility in healthy young males.